2019
DOI: 10.20344/amp.10768
|View full text |Cite
|
Sign up to set email alerts
|

Esquizofrenia: O Que o Médico Não Psiquiatra Precisa de Saber

Abstract: Schizophrenia is a disabling and severe mental illness that affects all social classes and racial and ethnic groups, spreading across every part of the world. It’s more frequent in males and it usually manifests itself in late adolescence or early adulthood and its early detection by all clinicians is important so that there is a proper referral to specialized psychiatric care. This article intends to update the knowledge regarding the diagnosis, treatment and prognosis of schizophrenia, with an emphasis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
5
0
4
Order By: Relevance
“…The level of functioning is markedly below the level previously achieved, in areas such as interpersonal relationships, work, or self-care, for a considerable period of time [1]. Cognitive and affective symptoms that worsen functional impairment are also common [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of functioning is markedly below the level previously achieved, in areas such as interpersonal relationships, work, or self-care, for a considerable period of time [1]. Cognitive and affective symptoms that worsen functional impairment are also common [2].…”
Section: Introductionmentioning
confidence: 99%
“…Negative symptoms were pointed out in a systematic review of the literature as persistent predictors of worse functioning when compared to positive symptoms [18]. It is also known that each relapse further worsens the previous functional level [2]. Another systematic review of the literature found that functional impairment in schizophrenia is not only related to mental functions, but is also due to activity and participation domains [15], so it is important to assess factors related to these domains as well.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is characterized by the presence of positive and negative symptoms. Cognitive and affective symptoms are also common (Queirós, Coelho, Linhares, & Telles‐Correia, 2019). Affective deficits are important, as they may influence other domains (Kring, & Elis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Apresenta uma etiologia multifatorial, estando envolvidos fatores genéticos, bioquímicos, ambientais, entre outros, e pode causar alterações em funções importantes da vida de um indivíduo, como cognição, pensamento e comportamento. Ademais, é comum que antes dos 25 anos de idade e pode acometer todas as classes sociais(QUEIRÓS et al, 2019).…”
unclassified